تأثير الإجهاد الملحي في الإنبات والنمو الأولي للطراز الوراثي المحلي لنبات الحلبة Trigonella foenum-graecum L - عساف إبراهيم (Latakia University Journal -Biological Sciences Series, 2019)
تم تنفيذ هذا البحث في كلية الزراعة بجامعة الفرات خلال الموسم الزراعي 2007/2008 لاختبار قدرة الطراز الوراثي المحلي للحلبة على تحمل الإجهاد الملحي في مرحلتي الإنبات والنمو الأولي, تمت دراسة مؤشرات إنبات البذور في تراكيز ملحية من NaCl ( 0، 2، 4، 6، 8، 10، 12 مليموز/سم )، وذلك في الظروف المخبرية وتحت ظروف الزراعة في أصص، كما حسب معدل النمو في واحدة الزمن (Growth Rate /d ). بينت النتائج أن انبات بذور الحلبة المحلية تأثر بالملوحة بدءاً من التركيز 4 مليموز/سم، مع انعدامه في التركيزين 10-12 مليموز/سم, لكن نتائج دراسة معدلات النمو لم تسجل فروقا معنوية بين معاملة الشاهد ومعاملات التراكيز2، 4، و 6 مليموز /سم، على الرغم من الانخفاض المسجل في مؤشرات الإنبات لهذه التراكيز. The research was carried out during 2007/2008 seasons in the Faculty of Agriculture, Al- furat University. It aimed to determine the capacity of local Fenugreek genotypes toward salinity stress at two stages (germination and seedling growth). The study was carried using certain salinity concentrations (2, 4, 6) millimohs /cm of NaCl under in vitro and in vivo conditions. Also, growth ratio per time unit was calculated as (Growth Rate /d). Results showed that local fenugreek seeds were significantly affected by salinity, initially from 4 millimohs /cm concentration at germination stage. Moreover, starting from 10 millimohs /cm concentration, no germination was observed. On the other hand, by studying growth ratios, no significant differences were recorded between concentrations of (2, 4, 6 millimohs /cm) and control treatment, despite a considerable decrease in the germination index of studied concentrations.